Postoperative pain after primary endodontic treatment and retreatment of asimptomatic teeth - Petrović Violeta; Opačić-Galić Vanja; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2011)
Introduction. Postoperative pain may develop after chemomechanical preparation during endodontic treatment or retreatment. It is associated with acute apical periodontitis caused by bacteria penetrated from the root canal into the periapical tissue. The purpose of this study was to evaluate the incidence of postoperative pain during endodontic treatment after intracanal medication performed with calcium hydroxide (CH) paste or 1% chlorhexidine gel (CHX). Material and Methods. The study included 22 asymptomatic teeth in both male and female patients. Fourteen teeth had the diagnosis of pulp necrosis and the other eight were retreatment cases. The root canals were prepared by crown-down technique using K files and copious irrigation with 0.5% sodium hypochlorite (NaOCl). Intracanal dressing was performed using either calcium hydroxide paste or 1% CHX gel. Each medicament was placed in the root canals of eleven randomly selected teeth. The teeth were restored with temporary filling. Postoperative pain was registered during the seven day period between two appointments. The level of pain was rated as follows: no pain, mild pain, moderate pain and severe pain (flare-up). The obtained data was analyzed using Fisher exact test. The level of significance was α=0.05. Results. Postoperative pain was absent in 77.3% of total number of treated teeth. Severe pain (flare-up) was registered in 2 cases (9%). There was no significant difference in pain incidence between the CH paste and CHX gel group (p=0.610). Conclusion. Endodontic procedure used in this study which considered root canal instrumentation and irrigation followed by intracanal medication with CH and CHX resulted in low incidence of postoperative pain.